Orco mediates olfactory behaviors and winged morph differentiation induced by alarm pheromone in the grain aphid, Sitobion avenae. (September 2015) - Fan, Jia; Zhang, Yong; Francis, Frédéric; Cheng, Dengfa; Sun, Jingrun; Chen, Julian
Abstract: Olfaction is crucial for short distance host location and pheromone detection by insects. Complexes of olfactory receptors (ORs) are composed of odor-specific ORs and OR co-receptors (Orco). Orcos are widely co-expressed with odor-specific ORs and are conserved across insect taxa. A number of Orco orthologs have been studied to date, although none has been identified in cereal aphids. In this study, an Orco gene ortholog was cloned from the grain aphid, Sitobion avenae, and named " SaveOrco "; RNA interference (RNAi) reduced the expression of SaveOrc o to 34.11% in aphids, resulting in weaker EAG (electroantennogram) responses to plant volatiles (Z-3-hexene-1-ol; methyl salicylate, MeSA) and aphid alarm pheromone (E-β-farnesene, EBF). Aphid wing differentiation induced by EBF was investigated in both RNAi treated and untreated aphids. EBF induced production of winged aphids in both pre-natal and post-natal periods in untreated aphids, but no such induction was observed in the RNAi-treated aphids. We conclude that SaveOrco is crucial for the aphid's response to pheromones and other volatiles, and is involved in wing differentiation triggered by EBF. Graphical abstract: Highlights: Orco gene clone and RNA interference were carried out in the gain aphid, Sitobion avenae. RNAi treatment resulted in significantly weaker EAG responses to pheromone and general volatiles. EBF induces winged morph during both pre-natal and post-natal periods of normal aphids but RNAi treated ones. RNAi treatment made aphids failed to response to behaviorally active odors, such as EBF, MeSA and Z-3-hexene-1-ol.